The determinants of two-dimensional service quality in the drinking water sector - Evidence from Colombia (2016)
Quality of drinking water service is considered in two dimensions: Tangibles (measured by sediment, taste, smell, and color) and reliability (measured by service continuity). Using a large and unique household-level dataset, we study important factors that are related to these dimensions in the Colombian drinking water sector. Based on the network design of pumping, purification, and delivery, our main findings are: (1) compared to users who do not receive a subsidy for water consumption, users who receive a subsidy report less reliable service while tangibles of water quality do not show significant difference between the reports of these two types of users; and (2) compared to water supplied by public providers, water supplied by community providers shows worse tangibles, while service reliability does not show significant difference between these two types of providers. These results suggest that Colombia water reform should not only aim to expand service and prompt water usage for the poor, but also strengthen quality control in multiple dimensions. © IWA Publishing 2016.